Review article: Vasileios MARINIS, Death and the Afterlife in Byzantium: The Fate of the Soul in Theology, Liturgy, and Art, Cambridge: Cambridge University Press, 2017 - ΠΑΤΕΔΑΚΗΣ Μανόλης (Byzantina Symmeikta, 2020)
Vasileios Marinis, Death and the Afterlife in Byzantium: The Fate of the Soul in Theology, Liturgy, and Art, Cambridge: Cambridge University Press, 2017